2006
DOI: 10.1101/gad.1390406
|View full text |Cite
|
Sign up to set email alerts
|

A KSR/CNK complex mediated by HYP, a novel SAM domain-containing protein, regulates RAS-dependent RAF activation in Drosophila

Abstract: RAF is a critical effector of the small GTPase RAS in normal and malignant cells. Despite intense scrutiny, the mechanism regulating RAF activation remains partially understood. Here, we show that the scaffold KSR (kinase suppressor of RAS), a RAF homolog known to assemble RAF/MEK/ERK complexes, induces RAF activation in Drosophila by a mechanism mediated by its kinase-like domain, but which is independent of its scaffolding property or putative kinase activity. Interestingly, we found that KSR is recruited to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
47
1
4

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(53 citation statements)
references
References 35 publications
1
47
1
4
Order By: Relevance
“…Activation of RAF kinase results in phosphorylation of its substrate MEK that can be detected by immunoblotting with an anti-phospho-MEK antibody. Using RNAi, we depleted endogenous dHYP and found that this abolishes MEK phosphorylation as reported (6) (Fig. 4E; SI Fig.…”
Section: Cnk/hyp Dimerization Is Essential For Raf Signaling In Vivomentioning
confidence: 99%
“…Activation of RAF kinase results in phosphorylation of its substrate MEK that can be detected by immunoblotting with an anti-phospho-MEK antibody. Using RNAi, we depleted endogenous dHYP and found that this abolishes MEK phosphorylation as reported (6) (Fig. 4E; SI Fig.…”
Section: Cnk/hyp Dimerization Is Essential For Raf Signaling In Vivomentioning
confidence: 99%
“…Good examples for this conclusion are Prohibitin, which is required for Ras-induced Raf-MEK-ERK activation and epithelial cell migration, 54 Shoc2/Sur8, which functions in complex with the catalytic subunit of protein phosphatase 1 as M-Ras effector modulating Raf activity 55 and Hyphen, which in Drosophila is part of a novel Raf controlling complex consisting of the scaffold KSR and the Raf binding protein CNK. 56 In these multiprotein complexes Raf proteins may act as true kinases, but kinase-independent, scaffolding-like functions of Raf kinases have also been described. Work from several groups established that homo-and heterodimerization of Raf kinases clearly exist, [57][58][59] and that heterodimerization can be Ras induced.…”
mentioning
confidence: 99%
“…De plus, des travaux récents ont montré que SHP-2 entre en jeu dans la déphosphorylation d'un résidu phosphotyrosine de SPRY nécessaire pour ses effets inhibiteurs. Ceci suggère donc un autre mode par lequel le complexe GAB/SHP-2 modulerait la signalisation [24]. Des études sur des souris chez lesquelles le gène KSR1 fut inactivé ont confirmé son rôle dans la signalisation RAS/MAPK et ont montré que l'inactivation du gène provoque une perturbation du développement de tumeurs mammaires ou de papillomes RAS dépendants [25,26].…”
Section: Apport Des Modèles Génétiquesunclassified
“…Des travaux récents de notre laboratoire ont montré que l'activité de CNK est régie par la tyrosine kinase Src42A (famille des kinases Src) [29]. Quoique le recrutement de RAF à CNK semble direct, celui de KSR/MEK à CNK fait intervenir une autre protéine appelée HYP (Hyphen ou AVE, Aveugle) [24]. Cette dernière n'est constituée que d'un domaine SAM (sterile alpha-motif) qui hétérodimérise avec le domaine SAM de CNK [30].…”
Section: Apport Des Modèles Génétiquesunclassified
See 1 more Smart Citation